Functionalized Nano-adsorbent for Affinity Separation of Proteins - Xueyan Zou; Fengbo Yang; Xin Sun; Mingming Qin; Yanbao Zhao; Zhijun Zhang (Nanoscale Research Letters, 2018)
Abstract Thiol-functionalized silica nanospheres (SiO2-SH NSs) with an average diameter of 460 nm were synthesized through a hydrothermal route. Subsequently, the prepared SiO2-SH NSs were modified by SnO2 quantum dots to afford SnO2/SiO2 composite NSs possessing obvious fluorescence, which could be used to trace the target protein. The SnO2/SiO2 NSs were further modified by reduced glutathione (GSH) to obtain SnO2/SiO2-GSH NSs, which can specifically separate glutathione S-transferase-tagged (GST-tagged) protein. Moreover, the peroxidase activity of glutathione peroxidase 3 (GPX3) separated from SnO2/SiO2-GSH NSs in vitro was evaluated. Results show that the prepared SnO2/SiO2-GSH NSs exhibit negligible nonspecific adsorption, high concentration of protein binding (7.4 mg/g), and good reused properties. In the meantime, the GST-tagged GPX3 separated by these NSs can retain its redox state and peroxidase activity. Therefore, the prepared SnO2/SiO2-GSH NSs might find promising application in the rapid separation and purification of GST-tagged proteins.